Developing a user centric mobile application - Es, Pepijn Levi Van (2023)
This report investigates the potential of using a newly developed mobile app, SuperPoupa, to assist Portuguese consumers in mitigating the financial burden posed by increasing food prices caused by global events. Surveys have determined a willingness to adopt SuperPoupa into consumers’ grocery habits, showing signs for an entrepreneurial opportunity. Core to the competitive edge of SuperPoupa is the self-build price-optimization algorithm to find the cheap est grocery basket. The report demonstrates the technical architecture and development process of the app's front- and back-end. Further deployment, research and development is necessary to evaluate the viability of SuperPoupa on larger scales.